2021
DOI: 10.1016/j.jphotochem.2020.113112
|View full text |Cite
|
Sign up to set email alerts
|

Influence of in situ photo-induced silver nanoparticles on the ageing of acrylate materials

Abstract: The present work aims to investigate the impact of a low amount of photo-induced silver nanoparticles (0.2 and 0.4 wt.% of Ag NPs) on the stability of acrylate materials (carriers of ester and ether groups) under the combined effect of oxygen and light. Different techniques were implemented to monitor the structural changes at different scales. The determination of the influence of AgNPs required a preliminary investigation of the pure acrylate polymer under the same experimental conditions. The polymer underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Southward et al observed such behavior when heating a non-conductive surface (Ag/polyimide films), from 300 • C to 340 • C, to form a conductive surface [7]. Moreover, the spherical Ag nanoparticles aggregated into more elongated shapes, as also shown by Bhattacharyya et al [34] and, more recently, by Zouari et al [35], which eventually created the Ag network found near the upper surface of the nanocomposite coating.…”
Section: Scanning Electron Microscopymentioning
confidence: 84%
See 1 more Smart Citation
“…Southward et al observed such behavior when heating a non-conductive surface (Ag/polyimide films), from 300 • C to 340 • C, to form a conductive surface [7]. Moreover, the spherical Ag nanoparticles aggregated into more elongated shapes, as also shown by Bhattacharyya et al [34] and, more recently, by Zouari et al [35], which eventually created the Ag network found near the upper surface of the nanocomposite coating.…”
Section: Scanning Electron Microscopymentioning
confidence: 84%
“…It is interesting to note that the Ag/C ratio rose from 0.1 to 2.1 upon thermal annealing; this confirms the redistribution of these elements to the first nanometers of the surface of the sample. Furthermore, the possible decomposition of the polymer binder [ 35 ] could also indirectly contribute to the increase in the relative ratio of Ag in the surface layer.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, this growth is lesser than that of the control culture for the C. albicans microorganism, suggesting that the polymer matrix releases one or more compounds capable of inhibiting fungal growth. In a previous study [ 51 ], we demonstrated that the polymer matrix is capable of releasing several organic compounds due to photodegradation, including formic acid. This weak acid has been shown to exhibit antifungal properties.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid the use of harmful products or processes, a photoinduced approach has been developed to synthesize monometallic NPs in a photopolymerizable matrix by combining the photoinduced synthesis of metal NPs and the photo-cross-linking of monomers. …”
Section: Introductionmentioning
confidence: 99%